2021
DOI: 10.3390/biology10121359
|View full text |Cite
|
Sign up to set email alerts
|

Virus Mimetic Poly (I:C)-Primed Airway Exosome-like Particles Enter Brain and Induce Inflammatory Cytokines and Mitochondrial Reactive Oxygen Species in Microglia

Abstract: Viral infections induce extracellular vesicles (EVs) containing viral material and inflammatory factors. Exosomes can easily cross the blood-brain barrier during respiratory tract infection and transmit the inflammatory signal to the brain; however, such a hypothesis has no experimental evidence. The study investigated whether exosome-like vesicles (ELVs) from virus mimetic poly (I:C)-primed airway cells enter the brain and interact with brain immune cells microglia. Airway cells were isolated from Wistar rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…For example, some studies show how MAVS interacts and determines inflammasome activation when induced by soluble stimuli such as nigericin, poly (I:C), and ATP. This does not happen with particulate matter such as alum, silica, and MSU [ 71 ]. In addition, other publications in the literature suggest that MAVS contributes to the activation of NLRP3 if induced by viral infectious agents.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…For example, some studies show how MAVS interacts and determines inflammasome activation when induced by soluble stimuli such as nigericin, poly (I:C), and ATP. This does not happen with particulate matter such as alum, silica, and MSU [ 71 ]. In addition, other publications in the literature suggest that MAVS contributes to the activation of NLRP3 if induced by viral infectious agents.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…They can play important role in several processes, including intercellular communication, proliferation, differentiation, angiogenesis and modulation of the immune response [ 13 , 14 ]. Previous studies demonstrated that EVs are important in host-pathogen interactions, including immunomodulator presentation [ 15 , 16 ], immune activation [ 17 , 18 ], antiviral response [ 19 ] and infection promotion [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%